Kinetics of Oxidation of Propyl Ester of 3-Phenylacrylic Acid by Acid Dichromate - Mehta, S.B.; Shah, M.K.; Rathod, D.R. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of propyl ester of 3-phenyl acrylic acid by acid dichromate ions are studied. The order of reaction with respect to chromium(lV), ester and the hydrogen ions is one in each case. The rate decreases in the presence of manganous ions. Oxidation products of the ester (i) when the ester is in excess are benzaldehyde and propyl glyoxal ate and (ii) when acid dichromate is in excess it is benzoic acid. The effect of temperature on rates is studied and thermodynamic parameters are calculated. A probable mechanism for the reaction is suggested on the basis of the product analysis.